2015
DOI: 10.1080/02650487.2015.1077606
|View full text |Cite
|
Sign up to set email alerts
|

Doing good matters to consumers: the effectiveness of humane-oriented CSR appeals in cross-cultural standardized advertising campaigns

Abstract: This investigation contributes to the advancement of international advertising theory by developing a model of cross-cultural consumer responses to humane-oriented corporate social responsibility (CSR) appeals in advertising and by testing it using structural equation modelling with data from six countries (Germany, Switzerland, Austria, France, USA, and Chile). The model includes ad-, advertiser-, product-, and behaviour-related variables.Based on survey data from 924 subjects, the model received support in a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

4
44
0
2

Year Published

2016
2016
2022
2022

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 83 publications
(50 citation statements)
references
References 74 publications
4
44
0
2
Order By: Relevance
“…Perceived CSR refers to a company's commitment to its societal obligations. Detailed CSR information about a company can lead to higher awareness of its activities in this area (Bhattacharya and Sen 2004) and that this type of information is typically beneficial to a company's image (Diehl et al 2016). Service quality refers to a company's ability to produce or organize.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Perceived CSR refers to a company's commitment to its societal obligations. Detailed CSR information about a company can lead to higher awareness of its activities in this area (Bhattacharya and Sen 2004) and that this type of information is typically beneficial to a company's image (Diehl et al 2016). Service quality refers to a company's ability to produce or organize.…”
Section: Literature Reviewmentioning
confidence: 99%
“…The affective liking of CSR advertisements is one important driver for employees to evaluate the perceived organizational CSR engagement. For consumers, Diehl, Terlutter, and Mueller (2016) showed that the affective evaluation of advertising incorporating a CSR appeal led to more positive evaluations of the product as well as to a higher perceived social responsibility of the company. Another study conducted by del Mar Garc ıa-De los Salmones and Perez (2018), which analyzed the effectiveness of CSR advertising in the financial sector, also suggested that the more favourable the affective evaluation of CSR advertisements, the more favourable was the evaluation of the company.…”
Section: Company's Csr Communication As a Basis For Employees' Csr Evmentioning
confidence: 99%
“…Liking of the Ads (Diehl, Terlutter, and Mueller 2016) The ads of the organizational CSR engagement are likeable. The ads of the organizational CSR engagement are pleasant.…”
Section: Constructmentioning
confidence: 99%
“…Marketers are increasingly seeking ways to highlight ethicallyconscious product attributes, including environmental friendliness and ethical production standards (Chang, Zhang, & Xie, ; Diehl, Terlutter, & Mueller, ). Given this growing trend in marketing practice, research has surprisingly been slow to examine consumer characteristics, particularly religion, that inform one’s response to such appeals, as well as the potential negative effects that may result from consumption of ethical goods.…”
mentioning
confidence: 99%